Strengthening Internal Quality Auditors’ Effectiveness in Higher Education - Hariyanti, Dwi; Masidonda, Jaelani La; Litamahuputty, Jacomina Vonny; Situmeang, Mis Fertyno; Siahaya, Septina Louisa (Journal of Ecohumanism, 2025)
This study investigates the factors in the work environment that mediate the effects of internal quality auditors’ performance at private universities (PT) in the Maluku Region. This research uses a quantitative method and is the subject of research at private universities in the Maluku Region. Research implementation in 2021–2023. The research sample was an internal quality audit of 45 auditors with saturated sample criteria. The tool is inferential analysis using SEM with a PLS approach. The results showed that internal factors had the greatest total influence on the performance of internal auditors, amounting to 0.673, followed by work environment factors (0.384) and internal factors (0.168). Our findings highlight the importance of PT focusing on internal and external factors as well as a good work environment to encourage the performance of higher education institutions in Maluku. The study reveals that internal and external factors affect auditor performance at work. Work environment, independence, authority, technical competency, and work environment affect higher education internal audit performance. According to the attribution theory, work environment, independence, authority, and technical skill do not affect performance the most.